Unveiling the Key Demands: Exploring Tourism Student Needs at a Vocational School - St Asriati Am; Mety Todingan; Radiah Hamid; Saiful Saiful (Universitas Hamzanwadi, 2023)
Tourism plays a pivotal role by substantially boosting foreign exchange, highlighting its immense significance for the region. This study is aimed at exploring the target needs concerning the communicative competencies of tenth-grade tourism students at vocational institutions in Makassar. To delineate these needs, open-ended questionnaires focusing on three specific target need dimensions were directed toward the teaching faculty. The subsequent data were meticulously processed through reduction, display, and conclusion phases. The distilled findings shed light on three cardinal facets of students' target needs: 1. Necessities: A realm encompassing pivotal skills such as speaking, listening, writing, and reading in tandem with the indispensable teaching materials. 2. Lacks: This underscores the discernible voids in students' grammar and lexical repertoire. 3. Wants: A domain where students manifest an ardent aspiration to master oral communication skills. These revelations underscore the intertwined complexities of target needs in the pedagogy of the English language. Additionally, this investigative endeavor empowers educators in Makassar's vocational institutions with a compass to navigate the intricate landscape of tourism students' requisites. Such profound insights germinate the seeds for sculpting potent English language curricula, harmoniously resonating with the students' ambitions while adeptly bridging their skill deficits. In summation, this research not only augments the caliber of tourism pedagogy but also unfurls a roadmap for educators, equipping them with the acumen to meticulously tailor their instructional strategies, ensuring a holistic address of students' target needs.